The bridge functions of molten salts - Tasseven, Ç; González, LE; Silbert, M; Alcaraz, O; Trullàs, J (AMER INST PHYSICS, 2001)
The bridge functions of molten NaCl and AgI near melting were obtained by using the model potentials of Born-Huggins-Mayer for NaCl and Vashishta-Rahman for AgI. The calculations of the bridge functions involved molecular dynamics simulations, the extension of the procedure originally proposed by Poll [Phys. Rev. A 37, 1672 (1988)] and the numerical solution of the Ornstein-Zernike equations. The calculated bridge functions do not conform with the universality ansatz. They also differ from the bridge functions obtained for model electrolytes. Following the results obtained for electrolytes and those of this work for molten salts, it is conjectured that the universality ansatz for the bridge functions does not apply for systems whose attractive interactions play a decisive role in their structural ordering. (C) 2001 American Institute of Physics.
Keywords: INTEGRAL-EQUATION THEORY; HYPERNETTED-CHAIN APPROXIMATION; HARD-SPHERE FLUID; FREE-ENERGY MODEL; MULTICOMPONENT LIQUIDS; IONIC LIQUIDS; HNC EQUATION; ELECTROLYTES; POTENTIALS; Chemistry; Physics